Adversity and Resiliency: Athlete Experiences within U.S. College Sport - Weight, Erianne; Haroldson, Jack Mitchell; Harry, Molly; Rudd, Ellie (Journal of Intercollegiate Sport, 2024)
Research regarding the benefits and detriments of the U.S. collegiate sport governance structure are mixed. Guided by Richardson’s Resiliency Theory (2002), former athletes (n = 215) revealed specific themes of adversity experienced during college with the most prevalent including injury, time demands, and coach-athlete tension. Through interview, athletes noted adversity promoted their resiliency, facilitated grit/perseverance, enhanced teamwork and time management skills, and led to other forms of growth. This study extends our understanding of the long-term impacts of competitive sport participation in this context. This understanding is important for administrators seeking to maximize participant experiences and emulate, enhance, or reform the U.S. College Sport governance model.